Analysis of the Impact of Tax Administrative Sanctions and Taxpayer Awareness on Taxpayer Compliance in the MSME Sector - Widayanti; Nur Hidayah K Fadhilah (International Journal of Business, Economics, and Social Development, 2026)
This study investigates the influence of tax administrative sanctions and taxpayer awareness on taxpayer compliance in the Micro, Small, and Medium Enterprises (MSME) sector. Tax revenue plays a crucial role in supporting national development; however, taxpayer compliance among MSMEs in Indonesia remains relatively low despite their significant contribution to the economy. This condition highlights the importance of enforcement mechanisms and internal taxpayer factors in improving compliance behavior. Using a quantitative approach with a causal-comparative research design, this study involved 100 MSME business actors as both the population and sample. Data were collected through structured questionnaires and analyzed using IBM SPSS version 26. The analytical techniques applied included validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing through partial (t-test) and simultaneous (F-test) analyses. The results demonstrate that tax administrative sanctions have a significant positive effect on taxpayer compliance, indicating that stricter and more consistent sanctions enhance compliance behavior. Taxpayer awareness also shows a significant positive effect on taxpayer compliance, suggesting that a higher level of understanding and consciousness regarding tax obligations encourages voluntary compliance. Simultaneously, tax administrative sanctions and taxpayer awareness significantly influence taxpayer compliance in the MSME sector.